A Systematic Review of Factors Affecting Mental Health and Well-Being of Asylum Seekers and Refugees in Germany - Hajak, Vivien L.; Sardana, Srishti; Verdeli, Helen; Grimm, Simone (Frontiers in Psychiatry, 2021)
Background: Since the onset of the 2015 European refugee crisis, approximately 4.46 million people have sought asylum in the European Union, with Germany logging the largest share of all asylum applications. In addition to the severe adversities before and during flight, the process of settling into a new environment involves stressors that affect psychological well-being and mental health. The aim of this systematic review was to examine contextual factors during post-migration that influence the mental health and well-being of asylum seekers and refugees (ASRs) in Germany. Methods: Following PRISMA guidelines, a systematic review was conducted across multiple databases for English and German studies published between 2015 and 2020 with index keywords. Results: From a total of 303 articles, 156 duplicates were removed and, after title review, another 87 were excluded for not meeting the inclusion criteria. After assessing the abstracts of the remaining 60 articles, 39 were excluded. Full texts of 21 articles were assessed for eligibility and after excluding 8 articles, 13 articles were included in the review. The results demonstrate high rates of psychological distress among ASRs in Germany and the significant influence of contextual factors on their mental health and psychological well-being. The main risk factors for poor mental health are an uncertain asylum status and living in shared asylum accommodations, while employment is a protective factor. Separation from the nuclear family, lack of German language skills, integration issues and discrimination are also associated with poorer mental health. Conclusion: ASRs have high prevalence rates of psychological distress directly influenced by contextual factors in Germany. Based on these findings, policy makers are strongly recommended to apply preventive strategies to reduce mental health problems of ASRs in Germany.